Escalating costs of innovative medicines: perspective and proposals - Vallano, Antonio; Pontes, Caridad (Frontiers in Public Health, 2024)
Public healthcare systems are challenged by the soaring costs of medications that require increasing resources, often at the expense of other investments. The expanding pharmaceutical budget poses a threat to the allocation of funds for essential preventive and primary healthcare services, while also raising concerns about equitable access, particularly in models where patients bear part of the costs with out-of-pocket expenses. Proposals on how to ensure ongoing and long-term accessibility, efficiency, and financial stability are required.Escalating costs of medicines may be explained in part by the mismatch between the traditional value-based pricing and reimbursement frameworks and the type of clinical development of targeted therapies and precision medicine in clinical practice. New appraisal methods and managed access strategies should adapt to therapies addressing small populations and increased uncertainty. Fair pricing strategies, transparent healthcare investments based on problems and outcomes, regulatory reforms, international cooperation, and critically examining the drug acquisition model are potential solutions. Transitioning from an industry-driven pricing approach to a health-driven payment model aligns the cost of treatments with actual health outcomes, establishing a foundation for a healthcare system addressing immediate challenges and fostering long-term well-being.Acknowledging the lack of a universally applicable solution, practical implementation of interventions requires a reframing of the pricing and access system and adaption to the targeted therapeutic approaches. Balancing innovation with financial sustainability necessitates a collaborative, adaptive and transparent approach, as well as transitioning towards health-driven payment models, moving the focus from the cost of medications to the well-being of populations worldwide.